EFEKTIVITAS SISTEM PERADILAN PIDANADALAM PENANGGULANGAN TINDAK PIDANA NARKOTIKA DI INDONESIA - Andika Putra Emco; Fahmi Febriansyah; Dinda Aura Fitaloka (Tamilis Synex: Multidimensional Collaboration, 2025)
Combating narcotics crimes poses a serious challenge for the criminal justice system in Indonesia. This article examines the effectiveness of the criminal justice system, which includes the roles of the police, prosecutors, courts, and correctional institutions in addressing narcotics-related offenses. This study employs a normative and empirical juridical approach, analyzing relevant legal regulations and reviewing case data and field practices. The findings indicate that despite intensive law enforcement efforts, the effectiveness of the criminal justice system is still hindered by limited resources, weak inter-agency coordination, and the need for rehabilitative approaches toward drug users. Comprehensive reform of the criminal justice system is necessary, including strengthening the capacity of law enforcement institutions and optimizing restorative justice as an alternative to punishment.